Phrases in Arabic and Indonesian Language - Mubarak, Faisal; Rahman, Ahmad Abdul; Awaliyah, Mursyidatul; Wekke, Ismail Suardi; Hussein, Saifuddin Ahmad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
This research is about differences and similarities of phrase construction in Arabic and Indonesian. The approach in this paper was a descriptive qualitative analysis approach. The findings of this study revealed that some construction of the phrase structure is the same. Subordinative noun phrases are equivalent to idhafah in Arabic, Indonesian adjective phrases are similar to na'at in Arabic, Indonesian coordinative phrases are similar with athaf in Arabic and Indonesian prepositional phrases are similar to syibhul-jumlah in Arabic. However, there are differences between both languages which can be found in Idhafah in Arabic, some vocabulary cannot be called phrases in Arabic, and vice versa. Differences can also be found in the use of athaf letters in the equivalent of coordinative phrases. The differences are also found in the numeral phrases and murakkab adadi. Even taukid and tarkib majazi do not have the equivalent in Indonesian. The differences are not only due to structural aspects, but also by differences in cultural concepts and expressions. This study implies that errors can be predicted in the construction of Indonesian student phrases and the production of translations of Arabic phrases that are different from the construction of Indonesian phrases. The differences were found not only in the structure but also in differences in cultural concepts. This study shows that mistakes can be predicted from the formation of phrases and the translation of Arabic sentences that are different from the structure of Indonesian language.